Supply Chain Management: A Review of Approaches, Practices and Impact on Performance - Hajar Haddouch; Zitouni Beidouri; Mohamed El Oumami (International Journal of Supply Chain Management, 2019)
The Supply Chain Management (SCM) is a research area that has received a lot of attention from many researchers in different disciplines. The multidisciplinary origin of SCM has led to a variety of definitions and approaches. Despite the vast body of academic literature on the subject, there are few examples of successful SCM implementations. Indeed, the implementation of SCM requires the deployment of a set of practices that the company should establish to ensure its success. The implementation of SCM practices can impact the various components of the company's performance. The aim of this paper is to review the different definitions and approaches of the SCM, present the practices that allow companies to better manage their supply chain. Also analyze the various performance measures and the impact of SCM practices on the overall performance.